Evaluation of the Effects of Earthquakes on Radon and Total Electron Content Values and Meteorological Changes on the North Anatolian Fault Zone, Türkiye - Hawrami, Dawar; Külahcı, Fatih; Alalı, Ahmet Sait (My University, 2023)
A cross-correlation analysis is proposed to analyse the relationships of soil Radon-222 gas, Ionospheric Total Electron Content (TEC), and some meteorological variables with earthquakes from the North Anatolian Fault Zone, Türkiye, one of the most active fault lines in the World. Statistically important results are obtained for Earthquake-Rn gas changes and Seismo-Ionospheric Coupling. In addition, we think that this study will be an important step for further studies on earthquake precursors.
Keywords: Prediction; Radon; Earthquake; Cross-correlation; TEC; Meteorology; Precursor